Miscanthus rhizome rot: A potential threat for the establishment and the development of biomass cultivations - Covarelli, Lorenzo; Beccari, G.; Tosi, L. (2012)
Little is known about diseases of miscanthus, one of the most important possible bioenergy crops in the world. In 2007, in an experimental field located near Perugia (Central Italy), the failure of the establishment of a miscanthus crop was observed a few days after rhizome transplanting. Previous phytopathological studies revealed the presence of three pathogenic fungal species (Fusarium avenaceum, Fusarium oxysporum and Mucor hiemalis) causing miscanthus rhizome rot (MRR). In the present study, the incidence and the severity of the disease caused by the mentioned pathogens were assessed and their effect on some miscanthus growth parameters, as indicators of rhizome viability and quality, was determined. Two different inoculation methods (rhizome immersion in conidial suspension and rhizome planting into a contaminated soil) were also evaluated. All fungal species, in single and mixed inoculation, produced MRR and a significant reduction of the number of roots per rhizome and root and shoot length decrease was also observed. Although all the species were pathogenic, significant differences in virulence between the two inoculation methods and between pathogens were observed, with F. avenaceum and M. hiemalis being more virulent than F. oxysporum in both types of inoculations. These results suggest that the three pathogens colonized the rhizomes in the soil of origin and/or during their storage, resulting in the failure of the crop after plantation. Therefore, the commercialization of certified miscanthus rhizomes should be strongly recommended in order to obtain healthy miscanthus cultivations and to avoid the transmission of soil-borne pathogens between different areas. © 2012 Elsevier Ltd.